Blood Pressure Response in Miners Exposed to Chronic Intermittent Hypoxia in Chile - Lang, Morin; Paéz, Valeria; Maj, Giacomo; Silva-Urra, Juan; Labarca-Valenzuela, Cristián; Caravita, Sergio; Faini, Andrea; Cantuarias, Javier; Perez, Oscar; Bilo, Grzegorz; Parati, Gianfranco (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Limited information is available on blood pressure (BP) behavior in workers exposed to chronic intermittent hypoxia (CIH), and even less is known regarding effects of CIH on 24-h ambulatory BP in those affected by arterial hypertension at sea level (SL). The aims of this study were to assess clinic and 24-h ambulatory BP at SL and at high altitude (HA; 3,870 m above SL) in workers exposed to CIH, and to compare BP response to HA exposure between normotensive and hypertensive workers. Methods: Nineteen normotensive and 18 pharmacologically treated hypertensive miners acclimatized to CIH were included, whose work was organized according to a “7 days-on−7 days-off” shift pattern between SL and HA. All measurements were performed on the second and seventh day of their HA shift and after the second day of SL sojourn. Results: Compared to SL, 24-h systolic BP (SBP) and diastolic BP (DBP) increased at HA [+14.7 ± 12.6 mmHg (p < 0.001) and +8.7 ± 7.2 mmHg (p < 0.001), respectively], and SBP nocturnal fall decreased consistently (−4.1 ± 9.8%; p < 0.05) in all participants, with hypertensives showing higher nocturnal DBP than normotensives (p < 0.05) despite the current therapy. Also, heart rate (HR) nocturnal fall tended to be reduced at HA. In addition, the 24-h SBP/DBP hypertension threshold of ≥130/80 mmHg was exceeded by 39% of workers at SL and by 89% at HA. Clinic HR, SBP, and DBP were significantly higher on the second day of work at HA compared with SL, the increase being more pronounced for SBP in hypertensives (p < 0.05) and accompanied by, on average, mild altitude sickness in both groups. These symptoms and the values of all cardiovascular variables decreased on the seventh day at HA (p < 0.05) regardless of CIH exposure duration. Conclusion: Long history of work at HA according to scheduled CIH did not prevent the occurrence of acute cardiovascular changes at HA during the first days of exposure. The BP response to HA tended to be more pronounced in hypertensive than in normotensive workers despite being already treated; the BP changes were more evident for 24-h ambulatory BP. Twenty-four-hour ABP monitoring is a useful tool for an appropriate evaluation of BP in CIH workers.